A light-responsive RNA aptamer for an azobenzene derivative. Issue 4 (5th December 2018) - Lotz, Thea S; Halbritter, Thomas; Kaiser, Christoph; Rudolph, Martin M; Kraus, Leon; Groher, Florian; Steinwand, Sabrina; Wachtveitl, Josef; Heckel, Alexander; Suess, Beatrix
Abstract: Regulation of complex biological networks has proven to be a key bottleneck in synthetic biology. Interactions between the structurally flexible RNA and various other molecules in the form of riboswitches have shown a high-regulation specificity and efficiency and synthetic riboswitches have filled the toolbox of devices in many synthetic biology applications. Here we report the development of a novel, small molecule binding RNA aptamer, whose binding is dependent on light-induced change of conformation of its small molecule ligand. As ligand we chose an azobenzene because of its reliable photoswitchability and modified it with chloramphenicol for a better interaction with RNA. The synthesis of the ligand 'azoCm' was followed by extensive biophysical analysis regarding its stability and photoswitchability. RNA aptamers were identified after several cycles of in vitro selection and then studied regarding their binding specificity and affinity toward the ligand. We show the successful development of an RNA aptamer that selectively binds to only the trans photoisomer of azoCm with a K D of 545 nM. As the aptamer cannot bind to the irradiated ligand ( λ = 365 nm), a light-selective RNA binding system is provided. Further studies may now result in the engineering of a reliable, light-responsible riboswitch.